2016
DOI: 10.1139/er-2016-0007
|View full text |Cite
|
Sign up to set email alerts
|

Do hyperabundant Arctic-nesting geese pose a problem for sympatric species?

Abstract: Arctic-breeding geese are at record high population levels and are causing significant changes to some of their breeding and staging habitats. These changes could influence sympatric wildlife, but the nature and strength of these effects are unknown. Here, we review the interactions between geese and sympatric species and propose future research that could help to fill important knowledge gaps. We suggest that geese may be indirectly affecting other species through changes to nesting habitat, prey availability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 82 publications
(78 reference statements)
2
31
0
Order By: Relevance
“…At the regional scale, we found that bird density was typically higher in regions with high goose abundance further supporting the spatial overlap between shorebirds and geese (Flemming et al. ).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…At the regional scale, we found that bird density was typically higher in regions with high goose abundance further supporting the spatial overlap between shorebirds and geese (Flemming et al. ).…”
Section: Discussionsupporting
confidence: 86%
“…, Milakovic and Jefferies ) are known, but the potential indirect effects on other sympatric taxa, less so (Flemming et al. ). The highly vegetated tundra habitats used by geese also provide breeding habitat for many other bird species, especially migratory shorebirds (Brown et al.…”
Section: Introductionmentioning
confidence: 99%
“…Habitat loss elsewhere in the range and climate change are considered the biggest threats to Arctic shorebirds (Thomas, Lanctot, & Szekely, ); however, goose‐induced habitat alteration could be a contributing factor that has not yet been assessed adequately to understand its impacts range‐wide. Known lesser snow goose colonies occupy a relatively small proportion of the North American Arctic (Flemming et al., ); however, our results indicate that breeding geese can alter habitat well beyond the confines of the colony. Furthermore, non‐breeding light geese may influence habitat anywhere within their range, which covers approximately 26% of the Arctic in North America and includes large fractions of the Arctic's wetlands, where a majority of shorebirds breed (Flemming et al., ).…”
Section: Discussionmentioning
confidence: 52%
“…The increasing impact by waterfowl on high latitude lakes and ponds provides a prime example of how climate change has consequences at the interface of terrestrial and freshwater environments, and also between geographically separated ecosystems such as overwintering grounds and breeding grounds. Migrating birds, particularly geese, have been observed in increasing numbers in many Arctic regions (Flemming, Calvert, Nol, & Smith, ; Jefferies, Drent, & Bakker, ; Pedersen, Speed, & Tombre, ). Likewise, the Svalbard archipelago has experienced a dramatic increase in goose populations during the second half of the last century (Madsen et al., ).…”
Section: Introductionmentioning
confidence: 99%